(3bUjOI (B" (3GdOQ GdefKhQ aj PcQ GdHYK hGdfThQ (B"s ((3dESeGYjd Hf eMeO s)
(3ChdgG (B:s
(3ddg CYXe eeG LGd ai GdacQ hMceg ai GdHQGjG Mce ebJOQ ehdkG YXje Mcje hGMO UeO Mi bOje eRjO aGWQ GdaWQ s
(3BNQgG (B:s
(3CHjGJgG JSY YTQ HYOgG eGjI cdGgeG hYXI CHgi ef GdOQQ JeJ GdbUjOI GdeHGQcI HMeO Gddg JYGdi hYhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B3s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs